The Analysis of Language Styles Used In “Wonderful Indonesia Youtube Channel” - Anggreni, Ni Putu Sri Diva (Jurnal Penelitian Mahasiswa Indonesia, 2025)
This study aims to identify the language styles used on the YouTube channel Wonderful Indonesia. In this digital era, YouTube competes with television as a widely used platform in various countries. One of YouTube's advantages is that users can upload videos globally. YouTube is also an important platform for promoting services and tourism destinations, such as Bali, which is famous renowned for its tourism. The Wonderful Indonesia YouTube channel, which promotes tourism in Bali and other regions of Indonesia, has 155.000 subscribers and 522 videos. With a significant number of viewers and subscribers, this study analyzes the language styles used by the channel to attract a large audience. Six videos were selected for analysis: (1) “Discover Bali the Island of the Gods,” (2) “Traveling Safely in Bali's New Era,” (3) “Wonderful Indonesia Return to Bali Safely and Easily,” (4) “Wonderful Indonesia - The Harmony of Bali,” (5) “Wonderful Indonesia - We Love Bali,” and (6) “Wonderful Indonesia Bali.” Data collection techniques involve watching the selected videos, transcribing the content, and analyzing the language styles used. Researchers use observation sheets to gather data and determine the dominant language styles. This study uses a qualitative method, as the data collected consists of sentences from YouTube videos. Results show that two types of language styles are used: antithesis (1 sentence, 12%) and hyperbole (7 sentences, 88%). Hyperbole is found to be the more dominant language style in the promotional videos on the Wonderful Indonesia YouTube channel.